Leveraging Home‐Delivered Meal Programs to Address Unmet Needs for At‐Risk Older Adults: Preliminary Data. Issue 9 (12th June 2019) - Morris, Andrea M.; Engelberg, Jessa K.; Schmitthenner, Brenda; Dosa, David; Gadbois, Emily; Shield, Renee R.; Akobundu, Uche; Thomas, Kali S.
Abstract : BACKGROUND: Home‐delivered meal programs serve a predominantly homebound older adult population, characterized by multiple chronic conditions, functional limitations, and a variety of complex care needs, both medical and social. DESIGN: A pilot study was designed to test the feasibility of leveraging routine meal‐delivery service in two home‐delivered meal programs to proactively identify changes in older adult meal recipients' (clients') health, safety, and well‐being and address unmet needs. INTERVENTION: Meal delivery personnel (drivers) were trained to use a mobile application to submit electronic alerts when they had a concern or observed a change in a client's condition. Alerts were received by care coordinators, who followed up with clients to offer support and help connect them to health and community services. RESULTS: Over a 12‐month period, drivers submitted a total of 429 alerts for 189 clients across two pilot sites. The most frequent alerts were submitted for changes in health (56%), followed by self‐care or personal safety (12%) and mobility (11%). On follow‐up, a total of 132 referrals were issued, with most referrals for self‐care (33%), health (17%), and care management services (17%). Focus groups conducted with drivers indicated that most found the mobile application easy to use and valued change of condition monitoring as an important contribution. CONCLUSION: Findings suggest that this is a feasible approach to address unmet needs for vulnerable older adults and may serve as an early‐warning system to prevent further decline and improve quality of life. Efforts are underway to test the protocol across additional home‐delivered meal programs. J Am Geriatr Soc 67:1946–1952, 2019